2006
DOI: 10.1097/01.blo.0000201148.06454.ef
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted Total Knee Arthroplasty Using Patient-specific Templating

Abstract: Current techniques used for total knee arthroplasty rely on conventional instrumentation that violates the intramedullary canals. Accuracy of the instrumentation is questionable, and assembly and disposal of the numerous pieces is time consuming. Navigation techniques are more accurate, but their broad application is limited by cost and complexity. We aimed to prove a new concept of computer-assisted preoperative planning to provide patient-specific templates that can replace conventional instruments. Computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(116 citation statements)
references
References 38 publications
5
108
2
1
Order By: Relevance
“…With 90.7 % of knees in the current analysis within the ideal range, our results can be considered amongst the best yet noted. They are in line with other studies of PSI which reported improved alignment [16,30,38]. Although it should be noted that other studies have failed to show a clear advantage for PSI technology [24,32], and that one study with the technology employed in the current analysis observed only a fair rate of accuracy, with higher risk of error >3°in the sagittal plane [11], there does appear to be an overall trend for the superiority of these new technologies over earlier instrumentation methods.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…With 90.7 % of knees in the current analysis within the ideal range, our results can be considered amongst the best yet noted. They are in line with other studies of PSI which reported improved alignment [16,30,38]. Although it should be noted that other studies have failed to show a clear advantage for PSI technology [24,32], and that one study with the technology employed in the current analysis observed only a fair rate of accuracy, with higher risk of error >3°in the sagittal plane [11], there does appear to be an overall trend for the superiority of these new technologies over earlier instrumentation methods.…”
Section: Discussionsupporting
confidence: 67%
“…Patient-specific instrumentation (PSI), which uses anatomical data obtained primarily from pre-operative axial computed tomography (CT) or magnetic resonance imaging (MRI) to create disposable cutting jigs individualized to the patient's unique anatomy, was created with this goal [16].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the number of applications has grown drastically, both in academic and industrial environments. One can now find patient-specific guides for various surgical procedures such as total knee replacement (Hafez et al 2006, Lombardi et al 2008, total hip replacement (Hananouchi et al 2009), hip surface replacement , Raaijmaakers et a. 2010, Kunz et al 2010, intra-and extraarticular radius malunions (Leong et al 2010, Oka et al 2008, and distal femur osteotomy (Victor et al 2011), Fig.…”
Section: Patient-specific Surgical Guidesmentioning
confidence: 99%
“…It can also visually guide a surgical gesture such as the impaction of a hip implant (Blemker et al 2007). It can fully replace a standard instrument, becoming for example a patient-specific cutting block for total knee replacement (Hafez et al 2006). Finally, it can be left in the body, becoming a guiding implant to reposition bone fragments for periacetabular osteotomy (Anaya et al 2011) or distal radius osteotomy (Oka et al 2010).…”
Section: Patient-specific Surgical Guidesmentioning
confidence: 99%
See 1 more Smart Citation